Infodemic, Health Promotion Efforts, and Preventive Behavior During the COVID-19 Pandemic in Indonesia: A Quantitative Analysis Study - Kurniati, Desak Putu Y; Indrayathi, Putu Ayu; Pradnyani, Putu Erma; Ulandari, Luh Putu S; Januraga, Pande Putu; Yuliarti, Monika Sri; Santosa, Karina Samaria (UI Scholars Hub, 2023)
The coronavirus disease 2019 (COVID-19) is the first pandemic in history where technologies and social media are used on a large scale to make people safe, informed, productive, and connected. At the same time, these technologies enabled the rise of the infodemic, which endangered pandemic control. This study aimed to assess COVID-19 information exposure in the community, the efforts to find related information in online media, and COVID-19 preventive behavior. A cross-sectional study was conducted with 909 participants in Indonesia using the consecutive sampling technique. Data were collected using a questionnaire distributed through social media (WhatsApp, Instagram, and Facebook) and analyzed using univariate analysis, bivariate analysis (Chi-square test), and multivariate analysis (multiple logistic regression). The results showed that about 838 (92.2%) participants said they often or always obtain information about COVID-19 online, 662 (72.8%) participants stated that information from online sources increased their knowledge of the disease, and 728 (80.1%) said that online information enabled them to make preventive efforts. Marital status (AOR: 1.81, p-value = 0.002) and perceived susceptibility (AOR: 1.42, p-value= 0.011) were the most influential factors for COVID-19 preventive behaviors. Information sources and channels frequently accessed by the community must be professionally managed by the government as valuable tools for mitigating an epidemic or pandemic.